If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + 2) = 2 + -1(2t + -2) Reorder the terms: 3(2 + t) = 2 + -1(2t + -2) (2 * 3 + t * 3) = 2 + -1(2t + -2) (6 + 3t) = 2 + -1(2t + -2) Reorder the terms: 6 + 3t = 2 + -1(-2 + 2t) 6 + 3t = 2 + (-2 * -1 + 2t * -1) 6 + 3t = 2 + (2 + -2t) Combine like terms: 2 + 2 = 4 6 + 3t = 4 + -2t Solving 6 + 3t = 4 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. 6 + 3t + 2t = 4 + -2t + 2t Combine like terms: 3t + 2t = 5t 6 + 5t = 4 + -2t + 2t Combine like terms: -2t + 2t = 0 6 + 5t = 4 + 0 6 + 5t = 4 Add '-6' to each side of the equation. 6 + -6 + 5t = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 5t = 4 + -6 5t = 4 + -6 Combine like terms: 4 + -6 = -2 5t = -2 Divide each side by '5'. t = -0.4 Simplifying t = -0.4
| 10x-23=77 | | 2(3x+4)=2(4x+1) | | 4x^3+15x^2+37x+39=0 | | 3-2k=-9 | | 8v-10=105 | | (x+1)(x-7)=0 | | 8r^2-12r=0 | | 0=-16x^2+3x+1.3 | | 3x^2+34x+80=0 | | 18=3(d-1) | | 3-4(x+2)=15 | | x^3+x^2-x-1.7=0 | | 3a-32=-2a+23 | | 7(-6y+9)+4y=-13 | | (x*x)+(x*x)=36 | | 137-4x=23x+23 | | 20.4-2c=5 | | 4x+y+1=-y-2x+3 | | (a-b)(a^2+2ab+b^2)= | | 12y^2+2y=0 | | (2c-d)(2c^2+2cd+d^2)= | | 7-7x=29-21x | | 3x+10+x+2=2x+20 | | -3x+7=28 | | 3x-45=6 | | 7(n+6)+8(n+4)= | | 8(x+3)+14(x+2)=74 | | 3(6z-1)-4(z+9)=4(z+1) | | 0.02-2.6=5.38 | | p=3a+5b | | 4x-12=x+6 | | 5b*6b= |